The Impact of Capital Market in Economic Growth of Bangladesh - Al-Shams, Tanveer Muhammad; Ashraf , Aysha (Asian Accounting and Auditing Advancement, 2018)
This study examines the capital market’s compel on Bangladesh’s economic growth between 2002 and 2012. The Data has been collected from Security Exchange Commission reports, Dhaka Stock Exchange Review Reports, and Central Bank of Bangladesh Statistical Bulletin respectively. From this study, we are able to know the different roles and functions played by the capital market. Moreover, this study showed the trends of some capital market exogenous variables like market capitalization, the all market share index, market value of the transaction, number of deals, and inflation over the last ten years. The ordinary least square method of log-linear regression analysis was used to analyze the data. The result shows that the capital market has significantly impacted the GDP. It is concluded that the capital market in Bangladesh has the potential of growth-inducing. The study recommends that the government should restore confidence to the market through regulatory authorities by ensuring transparency, fair trading transactions and improve the market capitalization by encouraging more foreign investors to participate in the market, and also to increase investment instruments such as derivatives, convertibles, swap, and option in the market.